2009
DOI: 10.1186/1471-2458-9-269
|View full text |Cite
|
Sign up to set email alerts
|

Rubella seroprevalence among primary and pre- primary school pupils at Moi's Bridge location, Uasin Gishu District, Kenya

Abstract: Background: Rubella is an infectious and generally mild childhood viral disease. The disease is of public health importance because infection acquired during early pregnancy often results in foetal abnormalities that are classified as congenital rubella syndrome (CRS). The burden of rubella infection in most developing countries in not well documented because of limited epidemiological data. However, availability of an effective vaccine has made it necessary to have all the countries with no routine vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 10 publications
4
16
2
Order By: Relevance
“…Although our study agrees with some studies such as by Karakoc et al ( 23 ) that show no significant association of the outcome with economic status, low socio-economic status has also been seen to be associated with risk of rubella infection in other studies ( 24 , 25 ). Our study agrees with authors such as Kombich et al ( 25 ) that found no association between education and rubella infection.…”
Section: Discussionsupporting
confidence: 92%
“…Although our study agrees with some studies such as by Karakoc et al ( 23 ) that show no significant association of the outcome with economic status, low socio-economic status has also been seen to be associated with risk of rubella infection in other studies ( 24 , 25 ). Our study agrees with authors such as Kombich et al ( 25 ) that found no association between education and rubella infection.…”
Section: Discussionsupporting
confidence: 92%
“…A high social economic status, which implies good living conditions, has been found to be associated with a lower risk to acquire rubella i nfection [20]. As in studies undertaken in Kenya [14,19], an increase in age was associated with an increase in rubella sero-positivity. A large proportion of women in Tanzania are involved in farming activities and reside in villages, and they also tend to have their first pregnancy at a low age (15–24).…”
Section: Discussionmentioning
confidence: 95%
“…As expected, the proportion seropositive increased with age, but was lower than previous reports in the region. 4345 This may be due to differences in urban and rural populations, with lower population densities and risk of exposure in rural areas. Introduction of measles-rubella vaccines may increase the age of infection, 31 therefore a large number of susceptible youth is a cause for concern.…”
Section: Discussionmentioning
confidence: 99%